Problematics of Creative Accounting and Earnings Management in the Context of the Development of Accounting Theories - Bachtijeva, Diana (Buhalterinės apskaitos teorija ir praktika, 2021)
The beginnings of accounting can be found even in the 14st century, when trade transactions began to be recorded in the books of account. To this day, accounting has evolved at certain stages, depending on goals were set for the accounting for that period. In the article after concluding the analysis of scientific sources the following are presented: the stages of accounting development, which were influenced not only by different Anglo-Saxon, Germanic and Latin accounting systems, but also by economic and political factors; the influence of accounting on the development of accounting theories is revealed. The concept of positive accounting theory, assumptions for manipulating accounting and the concept and application methods of earnings management and creative accounting are presented. Based on the research, a model of multi-paradigm approach is presented, in which the methodologies of normative and positive accounting theory can be fully applied. The proposed complexity of methodologies can help to solve not only the problems of creative accounting and earnings management, but also other problems of the 21st century. accounting issues.
Keywords: creative accounting; earnings managemen; positive accounting theory